Portable and pico-scale linear generator for wave energy conversion - Memon, A.H. (IEEE Computer Society, 2014)
This paper presents the design of linear permanent magnet generator for wave energy conversion. The main focus is to design a linear generator which is simple, lightweight and produce 1000 W electric power. Various types of linear generators are studied such as; Transverse flux, vernier-hybrid and iron-cored. The air-cored linear permanent magnet generator is selected as it eliminates cogging force and problems present in existing linear generators. Three designs of proposed linear generator are presented. Finite Element Analysis (FEA) is used to determine the electromagnetic performance of the proposed designs of generator. The results for all designs shown are as per expected. Â© 2014 IEEE.